A heliostat integrated with a sun-position sensor for daylighting. (February 2019) - Luo, Geng; Li, Lei; Wang, Juntao; Wang, Wenmo; Song, Jifeng; Yang, Yongping
Abstract: People are pursuing high-efficient production and high quality of life. However, the dark and damp problem of the dark side of the house has not been solved well. In order to allow the residents to enjoy the sunshine of nature and make the building more energy-efficient and natural, this paper proposes a heliostat for daylighting. It operates based on a 2:1 transmission ratio mechanism integrated with a sun-position sensor. And this specific structure simplifies the control method since it works well as long as the sensor is just directed at the sun. A geometrical model of the heliostat concerning installation errors was built. And the heliostat's performance was analysis by the simulation. The feasibility of the heliostat was verified.